In Search of Radical Theology : Expositions, Explorations, Exhortations - Caputo, John D. (Book collections on Project MUSE., 2020)
"After a detailed analysis of just what radical theology means, as a concept and in its relationship to traditional theology, this volume offers a selection of essays written for both academic and wider audiences which show aim at catching radical theology in action, in the church and in the culture at large"--